Ooh la la! It's beauty day - O'Connor, Jane.; Preiss-Glasser, Robin (New York : Harper, 2010)
On her mother's birthday, Nancy gives her a total beauty makeover in the yard outside, which she has converted into a fancy salon.
Keywords: Beauty shops -- Fiction; Beauty culture -- Fiction; Vocabulary -- Fiction